First record of the leafhopper genus Zyginopsis Ramakrishnan & Menon (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species - Jiang, Hao; Zhang, Yalin (Zootaxa, 2016)
The erythroneurine leafhopper genus Zyginopsis Ramakrishnan & Menon (Hemiptera: Cicadellidae: Typhlocybinae) is reported for the first time from China, with descriptions and illustrations of two new species, Zyginopsis paraverticalis and Zyginopsis gracilis spp. nov., and one newly recorded species from China, Zyginopsis verticalis Ahmed n. rec. A key for identification of Chinese species (adult males) is provided.